Chemical Composition and Inhibitory Effect of the Essential Oil from Mentha Spicata Irrigated by Wastewater on the Corrosion of Aluminum in 1 Molar Hydrochloric Acid - Bensabah,F. (2013)
Mentha Spicata irrigated by wastewater from the city of Settat (Morocco) was tested as corrosion inhibitor of aluminum in 1 M HCl using polarization method and weight loss measurements. The inhibition efficiency of mentha spicata oil was calculated and compared. We note good agreement between these methods. The results obtained showed that the tested inhibitor reduces the kinetic process of corrosion of aluminum. Its efficiency increases with the concentration and attained 83,01% at 1800 ppm. The effect of temperature on the corrosion behaviour of aluminum in 1M HCl was also studied in the range 283 K and 313 K. The thermodynamic data of activation were determined. The analysis of mentha spicata oil obtained by hydro-distillation using gas chromatography (GC) showed that the major components are carvone 57.11 % and limonene 27.77%.